2023
DOI: 10.3389/fpsyg.2023.1149634
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems in unaccompanied young refugees and the impact of post-flight factors on PTSS, depression and anxiety–A secondary analysis of the Better Care study

Fabienne Hornfeck,
Jenny Eglinsky,
Maike Garbade
et al.

Abstract: BackgroundUnaccompanied young refugees (UYRs) show elevated levels of mental distress such as post-traumatic stress symptoms (PTSS), depression, and anxiety. The individual post-arrival situation in the host country plays an important role in increasing or reducing mental health risks for these vulnerable children and youth. The study aims at examining the impact of pre- and post-migration factors on the mental health of UYRs.MethodsA cross-sectional survey of N = 131 young refugees (81.7% male, M = 16.9 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This can sometimes exceed the effects of their past trauma exposure prior to and during their forced migration. Research has indicated that daily stressors can contribute to equal or even higher levels of depression, anxiety, and distress than the adversities that refugees experienced during their displacement (Behrendt et al, 2023; Hornfeck et al, 2023; Miller & Rasmussen, 2010). While the daily stressors that refugees face spans multiple domains, for example, acculturative stress, limited housing, threat of deportation, and restricted social capital, many interventions fail to adequately address them (Behrendt et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This can sometimes exceed the effects of their past trauma exposure prior to and during their forced migration. Research has indicated that daily stressors can contribute to equal or even higher levels of depression, anxiety, and distress than the adversities that refugees experienced during their displacement (Behrendt et al, 2023; Hornfeck et al, 2023; Miller & Rasmussen, 2010). While the daily stressors that refugees face spans multiple domains, for example, acculturative stress, limited housing, threat of deportation, and restricted social capital, many interventions fail to adequately address them (Behrendt et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a low level of depression indicates successful adaptation of refugee students and their positive psychological state. This indicates effective support from the university community, social integration, successful coping with stress and the development of adaptive strategies (Hornfeck, et al, 2023).…”
Section: Relevancementioning
confidence: 97%
“…Having fled their home countries and endured challenging and traumatic experiences, on reaching safe havens, their relief may be short lived as they begin to grapple with the realities of settling in unfamiliar environments (Brook, Ottemöller, 2020). After arrival in the host country, refugees usually continue to face many challenges and they suggest that the impact of war and forced migration on mental health is compounded or alleviated by the post-migration resettlement context (Hornfeck et al 2023;Hohne et al 2020). According to the World Health Organization, mental health problems, such as anxiety, post-traumatic stress, and depression, are higher among refugee populations than the general population (WHO Regional Office for Europe, 2018).…”
Section: )mentioning
confidence: 99%
“…Separation from the family in different locations pointed to the heavy emotional burden of learning for the families back in the country of the origin (Integration of young refugees in the EU, 2019). There are several studies about refugee children and adolescents which highlight the protective effect social support after resettlement for mental health and its importance for recovery after trauma (Hornfeck et al, 2023;Verelst et al 2022).…”
Section: )mentioning
confidence: 99%